1989
DOI: 10.1039/c39890000283
|View full text |Cite
|
Sign up to set email alerts
|

Silver trifluoromethanesulphonate as an S-deprotecting reagent for the synthesis of cystine peptides

Abstract: The acetamidomethyl (Acrn) group attached at the thiol function of cysteine was found to be cleaved quantitatively by treatment with silver trifluoromethanesulphonate in trifluoroacetic acid, this reagent being more effective than silver trifluoroacetate and cleaved the S-benzamidomethyl and the S-p-methoxybenzyl groups as well; this new S-deprotecting reagent has been used in the syntheses of oxytocin and chicken calcitonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…However MALDI-MS analysis indicated that decomposition of the formed Hg-thiolate compounds turned out to be more challenging and required longer reaction times and a larger excess of DTT when compared with the corresponding Ag-thiolates (data not shown). For this reason, we chose to stick to the AgOAc protocol, which also has been reported to be milder in the presence of sensitive amino acid residues (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…However MALDI-MS analysis indicated that decomposition of the formed Hg-thiolate compounds turned out to be more challenging and required longer reaction times and a larger excess of DTT when compared with the corresponding Ag-thiolates (data not shown). For this reason, we chose to stick to the AgOAc protocol, which also has been reported to be milder in the presence of sensitive amino acid residues (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…The crude reaction mixture was directly subjected to MFD. Happily, Cys 34 was smoothly reduced to Ala 34 (3→4) whereas the Thr 54 -SEt functional group remained intact. NCL of fragments 3a (6) and 4a (7) followed by treatment with MeONH 2 •HCl provided polypeptide 8 with all of the cysteine residues deprotected.…”
Section: Synthesis Of the Gm-csf Aglyconementioning
confidence: 99%
“…They are also quite stable to HF at low temperatures but cleaved at higher temperatures in the presence of scavengers. 335 They are also stable to Ag (I) trifluoromethanesulfonate in TFA, 344 which quantitatively removes the S-Mmt group, and also to iodine oxidation. Other possible cleavage conditions are listed in the table.…”
Section: Protecting Groups Removed By Acidmentioning
confidence: 99%
“…343 It can be selectively removed in the presence of Meb using Ag(I) trifluoromethanesulfonate in TFA. 344 An intramolecular disulfide bridge between two Cys(Mob)-protected residues can be formed by removing the Mob group with MeSiCl 3 or SiCl 4 in TFA in the presence of diphenyl sulfoxide at 4ºC in 30 min. 345 In addition, oxidative removal with Tl(III) trifluoroacetate also leads to the formation of a disulfide bridge by reaction with a free Cys side chain.…”
Section: Protecting Groups Removed By Acidmentioning
confidence: 99%
See 1 more Smart Citation